Evaluación del potencial turístico como alternativa de Desarrollo Económico del centro poblado San José, distrito De la Banda de Shilcayo, provincia y región San Martín, año 2014 - Gaviria Diaz, Flor Isabel (2015)
The research entitled "Assessment of tourism potential as an alternative economic development of the town San Jose downtown, district Shilcayo, San Martín province and region, 2014, aims to characterize the main tourist resources having the town center, identify the types of tourism that are already underway, impacts that could result in the development of this activity and assess the interest of the general public to participate in tourism, all as alternative of a new activity to improve the conditions for economic development of the town. The research raised by the research is applicative, descriptive, observational and not experimental and the level of research is exploratory and explanatory and as a place to research the Town Center San José and the population represented by the 117 inhabitants, being the unit of analysis all persons of age registered in the register of residents of the town center. After applying the methodological process and analyzed the results the following conclusions were determined: a. It has been found that the tourism potential of the Town Center San José district of La Shilcayo, an alternative economic development for its people, based on counts with 04 tourist attractions are the hot springs of Tiraco, Waterfalls Pishurayacu, Tears of the bride and Salto de la Bruja, which currently can be associated with the presence of residents who not only identify these attractive as potential for tourism, but already providing tourism services, although incipient still, as if guided , power, mobility and housing. b. Since tourism demand, villagers identified that tourists now come to visit the tourist attractions are mainly employed for discovering new places, issues associated with nature and natural resources; elements present in 04 attractive identified as potential to be exploited for tourism as an economic activity in the population center. This being a factor identified by the inhabitants are the reasons why tourists come, are therefore elements to be utilized in the promotion to attract and regulate the massive arrival of more tourists to the area. c. From a geopolitical point of view, its proximity to the city of Tarapoto, principal place of arrival of tourists to the region San Martin, complements the potential of these attractions to become an alternative economic development of populated San Jose downtown. d. The types of tourism are being developed in the town center San José is an alternative economic development for its inhabitants, because of the population and is dedicated to providing services to tourists who come to the town center, being the guiding service and feeding those most residents participating, so the services provided, albeit very tentative way, well constitute an alternative economic development, which can be enhanced by putting in value or improved infrastructure and services to access tourist attractions. e. The impact caused by the development of tourism in the populated central San José is an alternative economic development for its inhabitants, because the main economic activity is agriculture can be developed in a manner complementary tourism, and still the coffee growing its core product, this being an agroforestry crop tends to conserve forest resources is not very aggressive about deforestation and therefore would have a strong additional boost in tourism for conservation and attractions the arrival of tourists to the area but has given way to some residents begin to provide tourism services such as food, guide, transportation, not an activity that has to displace the main economic activity of the area, but rather constitutes a complementary activity or as an alternative for the inhabitants, especially for young people. f. The interest of the inhabitants for the development of tourism in the populated central San José is an alternative economic development for its people; because from the social point of view, the residents show their interest in participating in providing tourist services, this as a sideline of their activities currently performed mainly in agriculture. g. The tourism potential of the town center San José and the assessment of its tourist attractions for its residents by identifying and rooting for them, this activity may constitute a new form of territorial differentiation and core of this differentiation are attractive for visitors, who can be considered the intrinsic value for the development of any proposed development in tourism in the area. The recommendations that arise are referred to the need to implement a Tourist Intervention Plan that articulates local organized participation of the inhabitants with authorities and tour operators; implement a plan to preserve and conserve and develop new attractions those inquiries tourist visiting the town in order to understand the motivations for visiting the center, the socio cultural characteristics, levels of services required and based profile to that define a tourist route in the population center.